Fecal Microbiome Transplantation from Children with Autism Spectrum Disorder Modulates Tryptophan and Serotonergic Synapse Metabolism and Induces Altered Behaviors in Germ-Free Mice - Lu Xiao (American Society for Microbiology, 2021)
ABSTRACT To determine the relationship of the gut microbiota and its metabolites with autism spectrum disorder (ASD)-like behaviors and preliminarily explore the potential molecular mechanisms, the fecal microbiota from donors with ASD and typically developing (TD) donors were transferred into germ-free (GF) mice to obtain ASD-FMT mice and TD-FMT mice, respectively. Behavioral tests were conducted on these mice after 3 weeks. 16S rRNA gene sequencing of the cecal contents and untargeted metabolomic analysis of the cecum, serum, and prefrontal cortex were performed. Untargeted metabolomics was also used to analyze fecal samples of TD and ASD children. Western blotting detected the protein expression levels of tryptophan hydroxylase 1 (TPH1), serotonin transporter (SERT), and serotonin 1A receptor (5-HT1AR) in the colon and TPH2, SERT, and 5-HT1AR in the prefrontal cortex of mice. ASD-FMT mice showed ASD-like behavior and a microbial community structure different from that of TD-FMT mice. Tryptophan and serotonin metabolisms were altered in both ASD and TD children and ASD-FMT and TD-FMT mice. Some microbiota may be related to tryptophan and serotonin metabolism. Compared with TD-FMT mice, ASD-FMT mice showed low SERT and 5-HT1AR and high TPH1 expression levels in the colon. In the prefrontal cortex, the expression levels of TPH2 and SERT were increased in the ASD-FMT group relative to the TD-FMT group. Therefore, the fecal microbiome of ASD children can lead to ASD-like behaviors, different microbial community structures, and altered tryptophan and serotonin metabolism in GF mice. These changes may be related to changes in some key proteins involved in the synthesis and transport of serotonin. IMPORTANCE The relationship between the gut microbiota and ASD is not yet fully understood. Numerous studies have focused on the differences in intestinal microbial and metabolism profiles between TD and ASD children. However, it is still not clear if these microbes and metabolites cause the development of ASD symptoms. Here, we collected fecal samples from TD and ASD children, transplanted them into GF mice, and found that the fecal microbiome of ASD children can lead to ASD-like behaviors, different microbial community structures, and altered tryptophan and serotonin metabolism in GF mice. We also demonstrated that tryptophan and serotonin metabolism was also altered in ASD and TD children. Together, these findings confirm that the microbiome from children with ASD may lead to ASD-like behavior of GF mice through metabolites, especially tryptophan and serotonin metabolism.